Voluntary approaches, market structure and competition - Rinaldo Brau; Carlo Carraro (Fondazione Eni Enrico Mattei (FEEM), 1999)
This paper surveys the recent literature devoted to the analysis of the interactions between the adoption of voluntary or negotiated agreements as a tool of environmental policy and market structure. The goal of this survey is twofold. On the one hand, we would like to identify the market environment which is most favourable to the adoption of voluntary approaches, namely whether these are more likely to be signed within industries that are more or less concentrated. On the other hand, we aim at assessing the effects of voluntary approaches on market structure and industry concentration. Our findings suggest that the signature of voluntary approaches is favoured by a situation in which industry is more concentrated. Moreover, the adoption of voluntary approaches is likely to further increase industry concentration. This clearly raises a trade-off between environmental benefits and economic costs provided by the adoption of voluntary approaches that must be dealt with an appropriate policy-mix.
Keywords: L1; L59; Q00; Q28; 330; Environmental regulation; Voluntary approaches; Market structure; Competition; Umweltpolitik; Selbstverpflichtung; Marktstruktur; Wettbewerb; Markteintritt; Spieltheorie; Theorie